Utility of Japanese encephalitis virus subgenomic replicon-based single-round infectious particles as antigens in neutralization tests for Zika virus and three other flaviviruses - Atsushi Yamanaka (2018)
© 2017 Elsevier B.V. The introduction of a foreign virus into an area may cause an outbreak, as with the Zika virus (ZIKV) outbreak in the Americas. Preparedness for handling a viral outbreak involves the development of tests for the serodiagnosis of foreign virus infections. We previously established a gene-based technology to generate some flaviviral antigens useful for functional antibody assays. The technology utilizes a Japanese encephalitis virus subgenomic replicon to generate single-round infectious particles (SRIPs) that possess designed surface antigens. In the present study, we successfully expanded the capacity of SRIPs to four human-pathogenic mosquito-borne flaviviruses that could potentially be introduced from endemic to non-endemic countries: ZIKV, Sepik virus, Wesselsbron virus, and Usutu virus. Flavivirus-crossreactive monoclonal antibodies dose-dependently neutralized these SRIPs. ZIKV-SRIPs also produced antibody-dose-dependent neutralization curves equivalent to those shown by authentic ZIKV particles using sera from a Zika fever patient. The faithful expression of designed surface antigens on SRIPs will allow their use in neutralization tests to diagnose foreign flaviviral infections.